Before Addiction: The Medical History of Alcoholism in Nineteenth-Century France - Saxton, Lauren (2015)
In 1849 a Swedish physician coined the term alcoholism, but it was not until the advent of the Third Republic that French physicians began to give shape to this new disease. This work explores the medical facts physicians presented concerning alcohol consumption from the disease's inception up until the outbreak of World War I, when regulation of alcohol consumption changed dramatically. It works to uncover the links between social anxieties and medical thought, and argues that physicians created a complex relationship between alcoholism and personal responsibility over these years. This relationship privileged bourgeois styles of consumption, undermined the cultural preferences of the working class, and perpetuated pre-existing medical and social beliefs concerning women. Critically, these physicians did not formulate a theory of addiction, which significantly changed the ways in which they understood the motives of drinkers, and the ways in which they evaluated a drinker's personal responsibility in a variety of spheres, both criminal and civil